A Study of the Thermal Efficiency of A Double-Air Inlet Doors Charcoal Stove - ธีระเจตกูล, วศิษฐ; ดีหลี, อนุชา; จันทร์วิเศษ, เผด็จ (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2019)
The objectives of this research were to study the effects on thermal efficiency of the amount of air entering through a double-air inlet doors charcoal stove. The experiment method was carried out following the WBT. The trials were divided into three phases: Trials on the high power (cold start), trials on the high power (hot start) and trials at low power (simmering). Four Trials were conducted. The first trial opened only one of the two inlets fully (100 %, 0 %). The second trial fully opened both inlets (100 %, 100 %). The third trial opened both inlets by half (50 %, 50 %). The last trial used a pot cover in addition to the third trial. The test results indicated that the thermal efficiency of the third trial increased to 42.75 %, higher than the first trial (19.50 %). The condition to slow down the exhaust gas by the pot cover in the last trial gave the highest efficiency value of 50.75 % and the combustion temperature was higher, also the specific fuel consumption was decreased.